2020
DOI: 10.33549/physiolres.934610
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Mass Spectrometry Analysis of the Sertraline Residues Contained in the Tissues of Rainbow Trout Reared in Model Experimental Conditions

Abstract: The growing consumption of pharmaceuticals in the human population and the insufficient efficiency of their elimination in waste water has a long-term negative impact on the environment of aquatic ecosystems, including the organisms that inhabit them. A significant contributor is the consumption of anti-depressants from the SSRI group, which corresponds to their increasing concentration in the environment. The aim of this work was to determine if antidepressant sertraline is able to be stored in fish organisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…3). Studies of PhACs analysis in wild fish and fish exposed to different concentrations of PhACs have shown that the liver tends to have a higher accumulation of compounds compared to other tissues (Grabicová et al, 2020(Grabicová et al, , 2017Vaclavik et al, 2020;Xie et al, 2015;Yin et al, 2021). This could be related to the liver being the main metabolizing organ in fish (Yin et al, 2021).…”
Section: Occurrence and Concentrations Of Compounds By Tissue/body Fl...mentioning
confidence: 99%
See 2 more Smart Citations
“…3). Studies of PhACs analysis in wild fish and fish exposed to different concentrations of PhACs have shown that the liver tends to have a higher accumulation of compounds compared to other tissues (Grabicová et al, 2020(Grabicová et al, , 2017Vaclavik et al, 2020;Xie et al, 2015;Yin et al, 2021). This could be related to the liver being the main metabolizing organ in fish (Yin et al, 2021).…”
Section: Occurrence and Concentrations Of Compounds By Tissue/body Fl...mentioning
confidence: 99%
“…One of the reasons could be that this matrix has a high ME, especially in suppressing the signal of the analytes. Grabicova et al (2018) reported that tissues with higher lipid Du et al, 2012;Brooks et al, 2005;Grabicová et al, 2020Grabicová et al, , 2018Grabicová et al, , 2017Grabicová et al, , 2014Lajeunesse et al, 2011;Liu et al, 2018Liu et al, , 2014Ramirez et al, 2009;Tanoue et al, 2015;Vaclavik et al, 2020;Xie et al, 2015) Sotalol <LOQ-7.9 --Terbutryn 2.a --Telmisartan 2.a 1.6-6.2 (Grabicová et al, 2020(Grabicová et al, , 2018) Venlafaxine 32.7 0.9-20.8 (Arnnok et al, 2017;Duarte et al, 2023;Grabicová et al, 2020Grabicová et al, , 2018Grabicová et al, , 2017Grabicová et al, , 2014Lajeunesse et al, 2011;McCallum et al, 2017;Moreno-González et al, Grabicová et al, 2020Grabicová et al, , 2018) Sertraline 8.0-86.6 0.12-535 (Brooks et al, 2005;Grabicová et al, 2020Grabicová et al, , 2018Lajeunesse et al, 2011;Ramirez et al, 2009;Tanoue et al, 2015;Xie et al, 2015) (continued on next page) D.P. Manjarrés-López et al Environmental Pollution 324 (2023) 121374 content, such as the kidney, show a more significant matrix influence.…”
Section: Occurrence and Concentrations Of Compounds By Tissue/body Fl...mentioning
confidence: 99%
See 1 more Smart Citation